EFFECT OF FARMING SYSTEMS ON PATHOGEN INFECTIONS AND CONTENT OF PHENOLIC COMPOUNDS IN CARROT (DAUCUS CAROTA L. SUBSP SATIVUS (HOFFM.) ROOTS - B. Cwalina-Ambroziak; R. Amarowicz; J. Tyburski; M. Janiak; M. K. Nowak (Journal of Animal and Plant Sciences, 2014)
The health benefits of carrots are determined by their nutritional value, including total phenolic content. Phenolic compounds are accumulated, among others, in response to biotic stress. The objective of this study was to evaluate the severity of black rot, crater rot, Sclerotinia rot and soft rot on the roots of carrots cv. Koral grown in plantations under integrated and organic farming systems. Chemical analyses were performed to determine the content of phenolic acids in harvested carrot roots. Carrots were grown in 2010-2012 in seven plantations located in Godki, Taraskowo, Tomaszkowo, Zgniłobłoty, Królikowo, Mielno and Rywociny (Poland). Carrot roots with disease symptoms were encountered more frequently in integrated plantations. Chemical analyses revealed higher concentrations of phenolic compounds in organically grown carrots, in comparison with the integrated farming system. The organic farming system seems preferable for growing carrots.
Keywords: carrots; Daucus carota; roots; health status; pathogens; phenolic compounds